2020
DOI: 10.1088/2050-6120/ab77f4
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved endogenous chlorophyll fluorescence sensitivity to pH: study on Chlorella sp. algae

Abstract: To better understand pH-dependence of endogenous fluorescence of algae, we employed spectroscopy and microscopy methods, including advanced time-resolved fluorescence imaging microscopy (FLIM), using green algae Chlorella sp. as a model system. Absorption spectra confirmed two peaks, at 400–420 nm and 670 nm. Emission was maximal at 680 nm, with smaller peaks between 520 and 540 nm. Acidification led to a gradual decrease in the red fluorescence intensity with the maximum at 680 nm when excited by 450 nm laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
(70 reference statements)
2
14
0
Order By: Relevance
“…In this contribution, FLIM recordings showed that most of the fluorescence signal in the Fontinalis antipyretica was situated inside the cell chloroplasts of the moss leaves. In control conditions, moss leafs exhibited short fluorescence lifetimes (200-350 ps), which is in agreement with others [36,[45][46][47], as well as with our findings in algae [19,20]. In pine wood middle lamella, lignin was also shown to have a 300 ns lifetime.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this contribution, FLIM recordings showed that most of the fluorescence signal in the Fontinalis antipyretica was situated inside the cell chloroplasts of the moss leaves. In control conditions, moss leafs exhibited short fluorescence lifetimes (200-350 ps), which is in agreement with others [36,[45][46][47], as well as with our findings in algae [19,20]. In pine wood middle lamella, lignin was also shown to have a 300 ns lifetime.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with previous observations that the main fluorescence recorded naturally in all plants is derived from chlorophyll a, a lightabsorbing pigment [15]. Chlorophyll fluorescence is highly sensitive to changes in the functional state and we employed it previously as a biosensing tool for tracking algae responsiveness to environmental modulators [20]. In the presented study, heavy metal NPs Co and Cu significantly lowered the chlorophyll fluorescence intensity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations